2022
DOI: 10.1111/1755-6724.14936
|View full text |Cite
|
Sign up to set email alerts
|

Petrogenesis and Geodynamic Implications of Early Cretaceous (∼130 Ma) Magmatism in the Baingoin Batholith, Central Tibet: Products of Subducting Slab Rollback

Abstract: The Baingoin batholith is one of the largest granitic plutons in the North Lhasa terrane. Its petrogenesis and tectonic setting have been studied for decades, but remain controversial. Here we report data on geochronology, geochemistry and isotopes of Early Cretaceous granitoids within the Baingoin batholith, which provide more evidence to uncover its petrogenesis and regional geodynamic processes. The Early Cretaceous magmatism yields ages of 134.4–132.0 Ma and can be divided into I‐type, S‐type and highly fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 116 publications
0
9
0
Order By: Relevance
“…However, the field investigation revealed that the Kese granite primarily comprises granite and overlaps with Diqian granodiorite without a clearly defined boundary (Figure 2a). Based on the zircon U-Pb dating results, we infer that Kese granite was formed later than Diqian granodiorite (~134.4 Ma) [37]. [34]; (b) modified after [23]; (c) age data from [23,35,[37][38][39][40]).…”
Section: Petrography Of Kese Granitementioning
confidence: 88%
See 3 more Smart Citations
“…However, the field investigation revealed that the Kese granite primarily comprises granite and overlaps with Diqian granodiorite without a clearly defined boundary (Figure 2a). Based on the zircon U-Pb dating results, we infer that Kese granite was formed later than Diqian granodiorite (~134.4 Ma) [37]. [34]; (b) modified after [23]; (c) age data from [23,35,[37][38][39][40]).…”
Section: Petrography Of Kese Granitementioning
confidence: 88%
“…Based on the zircon U-Pb dating results, we infer that Kese granite was formed later than Diqian granodiorite (~134.4 Ma) [37]. [34]; (b) modified after [23]; (c) age data from [23,35,[37][38][39][40]).…”
Section: Petrography Of Kese Granitementioning
confidence: 88%
See 2 more Smart Citations
“…Strong Eu and Sr depletion (Fig. 8) requires extensive fractionation of plagioclase and/or K -feldspar (e.g., Hanson, 1978;Li et al, 2007;Li et al, 2022). The decreasing trends of TFe 2 O 3 and MgO concentrations with increasing SiO 2 (Fig.…”
Section: Fractional Crystallizationmentioning
confidence: 96%